Razão autocrática: ideologia e direção política na progressividade da autocracia burguesa brasileira (1930-1945) - Sartoretto, Leonardo [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
This thesis investigates the existence of a theoretical-ideological body procedurally formulated in the work of Alberto Torres, Oliveira Vianna and Azevedo Amaral, in order to provide elements of an autocratic praxis for the direction of Brazilian capitalism. Assuming the existence of an evolutionary reason not reached in the Brazilian formation, these authors used a corroded reason, through a hard core located in positivism, to elaborate methodological approaches, historical investigations and political propositions that would offer the way for the resumption of such a path. Finding historical-concrete mediation in Getúlio Vargas, especially after the seizure of power by the Liberal Alliance in 1930, although already intertwined even before this political-military movement, the systematic set of representations elaborated by these intellectuals became an ideopolitical matrix, guiding the changes that took place during that period. Becoming an enlightened social subject and instrumentally rationalizing the concrete contradictions generated by the movement of big coffee capital, Vargas, an individual who condensed all these autocratic class demands in his political leadership, carried out an autocratic-progressive form of development for capitalism that is, it increased the internal productive forces without breaking with its excluding socio-political face, thus reaching its specific stage: the hyper-late industrialization. In this thesis, therefore, we seek to solve two distinct but closely related problems, which are both the demystification of the reductionist nature of this ideology, going to the root of its falsifying constitution, as well as exposing the main moments of the autocratic-progressive form of development. , following the influence of those previously conceived constructions, elaborated as responses to the arbitrarily manipulative demands of this autocracy.

A presente tese investiga a existência de um corpo teórico-ideológico processualmente formulado na obra de Alberto Torres, Oliveira Vianna e Azevedo Amaral, com a finalidade de fornecer elementos de uma práxis autocrática para a direção do capitalismo brasileiro. Pressupondo a existência de uma razão evolutiva não alcançada na formação brasileira, esses autores utilizaram uma razão corroída, mediante núcleo duro localizável no positivismo, para elaborar abordagens metodológicas, investigações históricas e proposições políticas que ofereceriam o caminho para a retomada de tal percurso. Encontrando em Getúlio Vargas a mediação histórico-concreta, especialmente após a tomada do poder pela Aliança Liberal, em 1930, embora já imbricados antes mesmo desse movimento político-militar, o conjunto sistemático de representações elaborado pelos referidos intelectuais se fez matriz ideopolítica, norteando as transformações promovidas naquele período. Tornando-se um sujeito social esclarecido e racionalizando instrumentalmente as contradições concretas gestadas pelo movimento do grande capital cafeeiro, Vargas, indivíduo que condensou todas essas demandas autocráticas de classe em sua liderança política, levou a cabo uma forma autocrático- progressiva de desenvolvimento para o capitalismo brasileiro, isto é, incrementou as forças produtivas internas sem romper com sua face sócio-política excludente, alcançando, assim, seu estágio específico: a industrialização hiper-tardia. Nesta tese, procura-se, portanto, resolver dois problemas distintos, mas intimamente relacionados, que são tanto a desmistificação da natureza reducionista dessa ideologia, indo à raiz de sua constituição falseadora, bem como expor os principais momentos da forma de desenvolvimento autocrático-progressiva, acompanhando a influência daquelas construções previamente ideadas, elaboradas como respostas às demandas arbitrariamente manipuladoras dessa autocracia.
Autocratic reason: ideology and political direction in the progressivity of Brazilian bourgeois autocracy (1930-1945)
Keywords: Brazilian bourgeois autocracy; Ideological decay; Impoverished reason; Form of capitalist development; Positivist physicalism; Autocracia burguesa brasileira; Decadência ideológica; Razão empobrecida; Forma de desenvolvimento capitalista; Fisicalismo positivista